A single touch multi control switch / Noriziana Yusof and Sharipah Daud - Yusof, Noriziana; Daud, Sharipah (2005)
A single touch multi control switch is advantage design circuits that have been created to make life more easily and fun to people. This project is used in radio. With a single touch, we can operate the radio. In this project, the circuit that is used is a simple circuit. Components that we used in this circuit are a few different ICs, relays and transistors. In this report, a detailed description of the components used to implement the circuit together with the explanation of how the circuit operates. The proposed project will provide a better solution in radio or alarm system. The relay could thus be made to trigger an alarm or open the main door of a building